Increasing The Saliva Flow Rate In The Elderly Through The Semula Model (Elderly Mouth Gymnulation) - Satuti, Nindita Enhar; Fatmasari, Diyah; Eko Ningtyas, Endah Aryati; Rosdiana, Ika (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Background: Carry on age experiencing the aging process Where has an impact on the function of the body's organs decrease ( organ degeneration ) is good Because factor natural nor Because of disease. The decline that occurs influences functions in the body, one of them functions in the cavity mouth that produces saliva. The declining rate of saliva flow is caused by the existing decline function of salivary glands in the elderly. Research Objectives: Producing a Model Senam Mulut Lansia (SEMULA) in an effort to increase the function cavity mouth to rate saliva flow. Method: Research methods used in the research This is Research and Development (R&D). The quasi-experimental design used study This is a pre-test - post-test, non-equivalent control group design. Taking a sample with a total sampling technique with criteria inclusion and exclusion consists of group interventions and group control. Oral exercises _ were done for 21 days for the elderly. Results: Research results This shows that there is influence before and after given treatment good in group intervention (p-value = 0.000) and control (p-value = 0.027). Test no in pairs rate salivary show the p- p-value is 0.044 (<0.05), which is significant there is a difference in effectiveness between group interventions and groups control. There is possible improvement in the pre-test and post-test seen from the difference in the average of each group, where group intervention experienced an increase of 0.14 and in the group control only 0.05. Conclusion: Development of Model Senam Mulut Lansia (SEMULA) effective in increasing function rate saliva flow.